Hak Asasi Manusia atas Lingkungan yang Aman bagi Kehidupan dan Kesehatan: Peraturan Hukum, Tantangan Kontemporer dan Perspektif Komparatif - Leheza, Yevhen; Sinkevych , Olena; Kravtsova, Zorina; Kudriavtseva, Olena; Cherniak , Ievgeniia (Syariah: Jurnal Hukum dan Pemikiran, 2023)
Abstract: The purpose of the research is to disclose human rights to an environment safe for life and health. Main content. The article reveals relationship between the concepts of “human rights” and "citizen’s rights” in the environmental sphere, “ecological rights”, “ecological responsibilities” and “the human right to an environment safe for life and health”. The war initiated by Russia caused significant damage to the environment, social and industrial infrastructure, flora and fauna. Methodology: The methodological basis of the research is the dialectical method of scientific knowledge, through the application of this method considered were legal, functional, organizational and procedural aspects of the essence of human rights to an environment safe for life and health. Conclusions. The legal grounds for the allocation of ecological rights to a separate institution in the system of constitutional rights are singled out, and their definition is derived. It was emphasized that Ukrainian citizens and non-governmental organizations made a lot of efforts to document the damages. In particular, EcoAction and Environment People Law organizations collect and publish relevant data on an ongoing basis. Thus, the "EcoZagroza" platform regularly publishes estimates of damages caused by environmental crimes, these estimates are calculated by the State Environmental Inspectorate of Ukraine. Key words: human right, constitutional law, environmental conservation, environmental legislation, law.